PSIV-4 Program Chair Poster Pick: Determinants of red meat exclusion from diets in Canada. (30th November 2020) - Gunte, Kebebe E; White, Robin R; Aukema, Harold; McAllister, Tim A; Riediger, Natalie; Legesse, Getahun; McGeough, E J; Wittenberg, Karin; Ibrahim, Naser; Ominski, Kim
Abstract: Production of red meat including beef, pork, and lamb, has been associated with climate change and high intakes of these foods have been linked to risks of several leading chronic diseases. Reducing red meat consumption has been suggested as an option to address important health and sustainability challenges. Characterizing the sociodemographic factors associated with red meat consumption is an important first step in identifying strategies to translate information regarding sustainable food choices into policy and national dietary guides. The objective of this study was to characterize the demographic factors associated with the exclusion of red meat in consumer diets. Mixed-effects probit regression that accounts for the hierarchical structure of individuals clustered in ten provinces in 24-hr dietary recall data from the 2015 Canadian Community Health Survey (n = 10, 117) was used to identify factors associated with dietary choices. Despite growing public discourse regarding the elimination of red meat, the results indicate that fewer than 5% of Canadians reported excluding red meat from their diet. Sex, education level, and race/ethnicity had a significant effect on red meat exclusion with single females (P < 0.000), individuals with at least a Bachelor's degree (P < 0.001), and individuals who self-identified as African (P < 0.001), Asian (P < 0.001), and Oceanian (pP < 0.001) origin more likely to eliminate red meat. In contrast, households with children under age 25 (P < 0.001) were less likely to do so. The disparities in consumption patterns of red meat by sex, race/ethnicity, education, and family status can inform public education and policy initiatives using science-based information to improve the health and environmental sustainability associated with the Canadian diets.